Exploring the relationship between irritable bowel syndrome and psychosocial, demographic, and health factors in Syrian hospital settings - Jamal Ataya; Nour Swileh; Zaher Alchawa; Haya Kabboul; Raneem Alnassif Alsheikh; Nadim Schkeif; Hiba Khazma; Hiba Shok; Ahmad Wassouf (BMC Psychiatry)
Abstract Background Irritable bowel syndrome (IBS) is a prevalent and complex gastrointestinal disorder that profoundly affects patients’ quality of life. This study, the first of its kind in Syria, explores the intricate relationship between IBS and demographic factors, with a focus on gender, age, socioeconomic status, the presence of chronic diseases, and psychological status. Methods A cross-sectional study of 562 participants was conducted in Damascus to investigate the prevalence of IBS and its association with psychological distress. Participants were assessed using a structured questionnaire that collected data on demographic factors, chronic diseases, and psychological distress. Statistical analysis, including chi-square, t-tests and one-way Anova, were performed to identify associations between these factors and IBS prevalence. Results The results revealed a higher prevalence of IBS among females and participants aged 40–50. Socioeconomic status was found to play a significant role, with lower income levels correlating with a higher likelihood of IBS. Furthermore, participants with chronic diseases exhibited an elevated likelihood for IBS, emphasizing the importance of considering comorbidities in IBS management. IBS was strongly associated with psychological distress, with a higher prevalence of depression and distress among participants with IBS. Weight was also associated with IBS, with a higher BMI linked to an increased likelihood of the condition. Conclusion This study highlights the multifaceted nature of IBS, and underscores the need for a comprehensive approach that integrates the physical and psychological aspects of its assessment and management. While this research provides valuable insights, it also acknowledges its limitations and calls for further investigation to elucidate the underlying mechanisms of these associations and develop tailored interventions for participants with IBS.